The Indian Removal Act : forced relocation - Stewart, Mark, 1960 July 7- (Snapshots in history., 2007)
Profiles the "Trail of Tears," the forced removal of five Southeastern Native American tribes to land west of the Mississippi River during the winter of 1838 and 1839.